EKSEGESIS KEJADIAN 16 TENTANG MAKNA JANJI TUHAN KEPADA HAGAR - Lawrence Christian (STT Bethel The Way, 2021)
There are many stories written in the bible and one of them is the storyof Hagar in the middle of Abram ans Sarai’s family who have not had children. In Genesis 16 Hagar has a problem in his life so that he runs away from his problem, Gos meets him and gives a promise or hope for his problem. The purpose of thie research is to prove thar Dog made a promise to Hagar by means of an exegetical process. To complete this research, the resacrher used the descriptive-inductive method. The results of the research found the meaning of the promise that God gave to Hagar. The conclusion is that in every problem that exists, God lways has a way to solve it.